2020
DOI: 10.1111/febs.15452
|View full text |Cite
|
Sign up to set email alerts
|

Cluster exchange reactivity of [2Fe‐2S]‐bridged heterodimeric BOLA1‐GLRX5

Abstract: Mitochondrial BOLA1 is known to form a [2Fe‐2S] cluster‐bridged heterodimeric complex with mitochondrial monothiol glutaredoxin GLRX5; however, the function of this heterodimeric complex is unclear. Some reports suggest redundant roles for BOLA1 and a related protein, BOLA3, with both involved in the maturation of [4Fe‐4S] clusters in a subset of mitochondrial proteins. However, a later report on the structure of BOLA1‐GLRX5 heterodimeric complex demonstrated a buried cluster environment and predicted a redox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Two BolA3-Grx5 hetero-complexes can transfer their Fe 2 S 2 clusters to Nfu1 to form a Fe 4 S 4 cluster in FeS protein maturation [ 126 ]. A role in cluster trafficking was ruled out for BolA1-Grx5 because of its structurally buried cluster and the lack of transfer efficiency to common Fe 2 S 2 cluster acceptors, such as ferredoxins [ 123 ]. Patients with mutations in the Grx5 or the BolA3 gene suffer from variations of nonketotic hyperglycinemia with decreased lipoylation, likely caused by interruption of the cluster transfer pathway to the FeS protein lipoate synthase [ 110 ].…”
Section: Glutathione Glutaredoxins and Iron-metabolismmentioning
confidence: 99%
“…Two BolA3-Grx5 hetero-complexes can transfer their Fe 2 S 2 clusters to Nfu1 to form a Fe 4 S 4 cluster in FeS protein maturation [ 126 ]. A role in cluster trafficking was ruled out for BolA1-Grx5 because of its structurally buried cluster and the lack of transfer efficiency to common Fe 2 S 2 cluster acceptors, such as ferredoxins [ 123 ]. Patients with mutations in the Grx5 or the BolA3 gene suffer from variations of nonketotic hyperglycinemia with decreased lipoylation, likely caused by interruption of the cluster transfer pathway to the FeS protein lipoate synthase [ 110 ].…”
Section: Glutathione Glutaredoxins and Iron-metabolismmentioning
confidence: 99%
“…The cluster release protein complex that extracts the cluster from ISCU is formed by HSPA9 (a HSP70 protein), HSC20 (a DnaJ chaperon protein that acts facilitating the transferring from ISCU to Grx5), GRPE1 (the nucleotide exchange factor that cycles ATP on Ssq1 for cluster transfer), and Grx5 (a glutaredoxin that interacts with HSPA9 and transfers [2Fe-2S] clusters to target proteins) [ 28 ]. Even though it was previously suggested that BOLA1 might assist Grx5 in cluster delivery, new experimental evidence discarded the direct role for the heterodimer Grx5-[2Fe-2S]-BOLA1 in cluster trafficking at least in humans [ 29 ]. On the other hand, Nasta and coworkers showed that the human Grx5-BOLA3 complex can transfers [2Fe-2S] 2+ cluster to the apo form of NFU1 yielding, in the presence of a reductant, a (4Fe-4S) 2+ cluster [ 30 ], whereas NFU1 may transfer the latter complex to client proteins like aconitase [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Among the possible Fe 2+ mitochondrial chelators, the most quoted, because of its very high concentration in the mitochondrial matrix, given in the range of 10–14 mM, is glutathione (GSH). 12 It was proposed that a Fe 2+ -glutathione adduct ([Fe II (H 2 O) 5 GS] + ) is the major non-proteinacious LMM Fe complex in the mitochondrial matrix and that a glutathione-coordinated [Fe 2 S 2 (GS) 4 ] 2− complex might be also part of the mitochondrial LIP 10,11 a to be used as reservoir for the mitochondrial [Fe–S] cluster assembly machinery 13 as well as to be transferred to the cytosol. 5 However, the exact composition of the non-proteinacious LMM complexes detected in mitochondria still needs to be addressed.…”
mentioning
confidence: 99%